Володимиру Дмитровичу Бабкіну – 85 років - Горбатенко, В.П. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The article and other materials dedicated to the 85th anniversary of Volodymyr Dmytrovych Babkin.